Identification and analysis of bHLH transcription factor family in red raspberry based on transcriptome sequencing - HE Zhimin1,2, ZHANG Junxin1,2, YU Liping1,2, HU Kang1,2, JI Fengqi1,2, HUANG Tiran1,2, YANG Mingfeng1,2*, MA Lanqing1,2 (Guangxi Zhiwu)
bHLH transcription factors are a large family of transcription factors in plants, which play important roles in plant growth and development, secondary metabolism regulation, and hormone response. Red raspberry fruit is rich in raspberry ketone. To investigate the role of bHLH transcription factor in the growth and development of red raspberry and the synthesis of raspberry ketone, members of the red raspberry bHLH gene family were identified and bioinformatics analysis of these genes were performed based on transcriptome sequencing of two red raspberry fruits, ‘Polka' and ‘Orange Legend'. The results were as follows:(1)A total of 95 bHLH transcription factor family members were identified in red raspberry fruits.(2)Most of the bHLH transcription factor family members were unstable hydrophobic proteins; and more than half of them were localized in the nucleus.(3)bHLH transcription factor N-terminal contained the conserved His5-Glu9-Arg13 sequence and C-terminal contained the conserved Leu sequence.(4)The phylogenetic tree divided the family members into 20 subfamilies, of which the R subfamily had the most members with 12.(5)The expression pattern map indicated that the bHLH transcription factor was expressed at a higher level during the green fruit stage and at a lower level during the ripening stage. The results provide a basis for screening bHLH transcription factors that are consistent with changes in raspberry ketone content and provide a reference for further exploring the function of red raspberry bHLH family.